Investigation of deformation induced precipitation and the related microstructure evolution of Al–Zn–Mg–Cu alloy - Jinrong Zuo; Longgang Hou; Xuedao Shu; Wenfei Peng; Anmin Yin; Jishan Zhang (Materials Research Express, 2020)
As heating time, temperature, strain and strain rate are the four most commonly used controllable parameters in thermomechanical treatments of high strength aluminum alloy, which have great influence on microstructures and mechanical properties. 7055 Al alloy was subjected to solution and thermomechanical treatment (4 routes) at different heating time (route 1), temperatures (route 2), strains (route 3) and strain rates (route 4) to investigate their effects on grain structure and precipitation. The results show that MgZn _2 particles are almost completely dissolved back into the matrix after solution treatment, but the coarse Al _7 Cu _2 Fe and Al _2 CuMg remain steady. Particles preferentially precipitate at grain boundaries. Precipitates free zones appear after aging at 300 °C for different time in route 1. With the increased over aging time, precipitates grow and the quantity of rod-shaped increases. After hot deformation, grains are elongated and numerous deformation induced precipitates are formed. Grain width increases with the increase of strain temperature/rate in route 2 and route 4. However, with further strain, grain width first decreases and then increases with the minimum value taken at 60% deformation in route 3. Due to the effect of deformation on spheroidization and refinement of precipitates, the size of precipitates decreases with strain and is spheroidized gradually in route 2 compared with route 1. Strain energy plays the dominant role during over aging or at low strain leading the rod liked precipitates, with the increase of strain, interfacial energy plays the decisive role, and precipitates are spherical.